CCDC9 is identified as a novel candidate gene of severe asthenozoospermia. (2nd November 2019) - Sha, Yanwei; Xu, Yankai; Wei, Xiaoli; Liu, Wensheng; Mei, Libin; Lin, Shaobin; Ji, Zhiyong; Wang, Xu; Su, Zhiying; Qiu, Pingping; Chen, Jing; Wang, Xiong
ABSTRACT: Owing to less than 1% of motile spermatozoa in the ejaculated semen, severe asthenozoospermia is a serious threat to the male reproductive health. Herein, we identified a novel homozygous variant in CCDC9 (NC_000019.9: g.47763960C>T, NM_015603.3, NP_056418.1: p. Ser109Leu) in a patient from a consanguineous family. The variant was highly pathogenic and was predicted to be a candidate gene for asthenozoospermia through in silico analysis. The CCDC9 protein levels were significantly low and its morphology and ultrastructure were severely damaged in the spermatozoa containing the novel variant. Therefore, CCDC9 may be a novel pathogenic gene associated with severe asthenozoospermia. Abbreviations : CCDC9 : coiled-coil domain containing 9; AZS: asthenozoospermia; MP: midpiece; MS: mitochondrial sheath; ODF: outer dense fiber; CP: central pair; DMT: doublet microtubule; IDA: inner dynein arm; ODA: outer dynein arm.